RELATIONS AND CONTROL MECHANISMS BETWEEN THE LEGISLATURE AND THE EXECUTIVE BODIES IN THE MACEDONIAN CONSTITUTIONAL ORDER - Körbayram, Azam (International Scientific Journal Vision, 2021)
In the Macedonian constitutional order, which is close to the northern European type of government, the parliamentary government systems, where there is a soft separation of powers and the powers, especially the legislature and the executive, are intertwined in places, also have the authority to supervise the execution of the legislature in accordance with the spirit of parliamentarism. In other words, it is envisaged that the legislative executive has powers such as questions, interpellation, research and investigation commissions, and vote of confidence. In accordance with this philosophy and spirit, the Macedonian Constitution of 1991 gives these supervisory powers to the legislature, namely the parliament. However, in the face of these powerful and effective powers, the self-annulment of the legislature, that is, the institution of self-annulment. Therefore, in this article, these powers are briefly discussed one by one and it is discussed that it may be beneficial to rectify the legislative’s self-dissolving power as the executive’s power to dissolve the legislature in accordance with the principle of equality of powers. In this way, the constitution’s distribution of powers is in any case in line with the nature of the parliamentary government system and the understanding of the theory of separation of powers. The change in the traditional understanding of the parliamentary system hindered the active participation of political parties in the constitutional order and tended to change the balance. Particularly, disciplined parties are effective in this regard and have a great influence on the legislature. In this respect, we think that handling and arranging some legal regulations in the constitutional dimension can be effective in terms of the dynamism and distribution of authority of the system.